ANALISIS STRATEGI PEMASARAN PADA PT GOJEK INDONESIA - Yunita, Yunita; Kumbara, Vicky Brama; Andri Wijaya, Ronni (Jurnal Ilmu Manajemen Terapan, 2020)
Trends motorcycle online has increased in recent years with the increasing need for fast transportation in Jakarta. Ease and speed of motorcycles message via applications and the speed of travel (travel time) becomes a key factor many motorcycle enthusiasts online. Gojek as pioneers face challenges in maintaining quality service and win the competition. The marketing strategy is one way to determine the competitiveness of each force. Effective Use of SWOT can play an important role in determining the marketing strategy, in order to know the strengths, weaknesses, opportunities and threats faced by enterprise IT in maintaining the viability and continuity of the company. Issues to be resolved in this research is How to determine the internal and external factors which will affect the company's strategy and determine appropriate marketing strategy planning for Gojek. The research was conducted using the method of analysis of IFAs to analyze the internal factors, the analysis of EFAS to external factors, then, input into the model kuantittif ie SWOT matrix. Results of the analysis showed that, based on internal strengths and weaknesses, opportunities and external threats, four sets of strategic alternatives that may be taken by the manager of the company in the face of increasingly competitive. Standard nomenclature should be used and abbreviations should be avoided. No literature should be cited. The keyword list provides the opportunity to add keywords, used by the indexing and abstracting services, in addition to those already present in the title. Judicious use of keywords may increase the ease with which interested parties can locate our article